ALMA view of the circumnuclear disk of the Galactic Center: tidally disrupted molecular clouds falling to the Galactic Center. (27th July 2018) - Tsuboi, Masato; Kitamura, Yoshimi; Uehara, Kenta; Tsutsumi, Takahiro; Miyawaki, Ryosuke; Miyoshi, Makoto; Miyazaki, Atsushi
Abstract: We present high angular resolution and high sensitivity images of the "circumnuclear disk" (CND) and the surrounding region of the Milky Way Galaxy in the CS  J = 2–1, SiO v = 0 J = 2–1, H 13 CO + J = 1–0, C 34 S J = 2–1, and CH3 OH $J_{K_a, K_c}=2_{1, 1}$ –11, 0 A −− emission lines using ALMA. The CND is recognized as a torus-like molecular gas with gaps in these emission lines, except for the CH3 OH emission line. The inner and outer radii of the CND are estimated to be R in ∼ 1.5 and R out ∼ 2 pc, respectively. The velocities of the rotation and radial motion are estimated to be V rot ∼ 115 km s −1 and V rad ∼ 23 km s −1, respectively. The LTE molecular gas mass is estimated to be M LTE ∼ 3 × 10 4   M ⊙ . We also found some anomalous molecular clouds in the surrounding region. One of the molecular clouds is positionally connected to part of the CND adjacent to the "western arc." However, the cloud is seen to rotate in the opposite direction to the CND, so it could currently be falling from the outer region to the CND and being disrupted by the tidal shear of Sagittarius A* (Sgr A*) because the velocity is not yet assimilated into that of the CND. Another molecular cloud is continuously connected to the tip of the "eastern arm" (EA). The velocity of this cloud is consistent with that of the ionized gas in the EA. These facts suggest that the molecular cloud is falling from the outer region to the vicinity of Sgr A*, being disrupted by the tidal shear, and ionized by strong UV emission from the central cluster because the impact parameter of the cloud is smaller than the first cloud. These falling clouds would play an important role in transferring material from the outer region to the CND and/or the vicinity of Sgr A*.